The relationship between blood parameters related to lymphocytes in response to the treatment of idiopathic granulomatous mastitis - Hassan Moayeri; Kasra Moradi; Maryam Pourabbas Azizi; Danial Khezri (Mashhad University of Medical Sciences, 2023)
Introduction: Granulomatous inflammatory lesions of the breast can be considered as primary or idiopathic inflammation of the breast; therefore, investigating the relationship between inflammatory parameters including neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio can be useful in the prognosis of idiopathic granulomatous mastitis. The present study was conducted with aim to investigate the relationship between blood parameters related to lymphocytes in response to the treatment of idiopathic granulomatous mastitis (IGM). Methods: This prospective cohort study was conducted in 2020 on 34 patients with IGM referred to the breast clinic of Kurdistan University of Medical Sciences. The course of lymphocyte parameters with disease symptoms, diagnostic and treatment process were measured. For patients with a definite diagnosis of IGM, if there was a mass, aspiration was performed under ultrasound guidance, and needle sampling and routine tests, including complete blood count were performed. The evaluation time was at the beginning of the diagnosis, one month and 6 months after the complete blood count. Data analysis was done using SPSS statistical software (version 24) and variance analysis and Tukey tests. P<0.05 was considered significant. Results: There was no significant difference between the demographic variables of age and body mass index with the treatment outcome in the examined patients (P>0.05). Also, no significant relationship was observed between the variables of mass number, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio with the treatment outcome in the examined patients (P>0.05). Conclusion: According to the results, it can be said that referring to the mean ratio of neutrophil to lymphocyte and platelet to lymphocyte is not a reliable indicator to evaluate the response to the treatment of IGM.